1996
DOI: 10.1128/jvi.70.3.1618-1623.1996
|View full text |Cite
|
Sign up to set email alerts
|

The exogenous form of Jaagsiekte retrovirus is specifically associated with a contagious lung cancer of sheep

Abstract: Sheep pulmonary adenomatosis ([SPA] ovine pulmonary carcinoma) is a transmissible lung cancer of sheep that has been associated etiologically with a type D-and B-related retrovirus (jaagsiekte retrovirus [JSRV]). To date it has been impossible to cultivate JSRV in vitro and therefore to demonstrate the etiology of SPA by a classical approach. In addition, the presence of 15 to 20 copies of endogenous JSRV-related sequences (enJSRV) has hampered studies at the molecular level. The aim of this study was to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
45
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 36 publications
2
45
0
1
Order By: Relevance
“…Total RNA was extracted from pooled sucrose gradient fractions, from 100 l of concentrated nasal fluid, from 100 l of SPA lung fluid, or from 0.2 to 0.5 g of tissue by the acid guanidinium thiocyanatephenol-chloroform method (2). cDNA was synthesized by random-primed RT as described previously (15).…”
Section: Source Of Materialmentioning
confidence: 99%
See 3 more Smart Citations
“…Total RNA was extracted from pooled sucrose gradient fractions, from 100 l of concentrated nasal fluid, from 100 l of SPA lung fluid, or from 0.2 to 0.5 g of tissue by the acid guanidinium thiocyanatephenol-chloroform method (2). cDNA was synthesized by random-primed RT as described previously (15).…”
Section: Source Of Materialmentioning
confidence: 99%
“…gag PCR. The primers and conditions used for PCR of cDNA or of genomic DNA were exactly as described previously (15): P1 (sense), 5Ј-GCTGCTTTRA GACCTTATCGAAA-3Ј; and P2 (antisense), 5Ј-ATACTGCAGCYCGATGGC CAG-3Ј). PCR products were detected by electrophoresis through a 2% agarose gel in 1ϫ Tris-borate-EDTA buffer in the presence of 0.5 g of ethidium bromide per ml.…”
Section: Source Of Materialmentioning
confidence: 99%
See 2 more Smart Citations
“…JSRV has been classified as a type D retrovirus, based on genomic organization, but has a type B-like Env protein (61). The sheep genome carries multiple copies of JSRV-like endogenous sheep retrovirus (ESRV) sequences (25,27,61), but subsequent studies have shown that JSRV is an exogenous virus distinct from ESRV sequences (4,5,44) and is specifically associated with OPC. Recent studies by Palmarini et al (48) using an infectious molecular clone of JSRV have confirmed that JSRV is the causative agent of OPC.…”
mentioning
confidence: 99%